Change of Employee Status to Civil Servants in Indonesia (Comparative Legal: Village Secretary, Contract Employees, KPK Staff and BRIN Employees) - Imam AW Nuryamto (Budapest International Research and Critics University, 2022)
The transition of status from employee of public institution to civil servant in Indonesia often occurs and always raises legal and social problems. The legal system for the transition of status is not patterned. There are differences on the level of law/arrangements, conditions and methods, as well as the consequences of dismissal. Even the special nature of status transfer laws is the einmaligh and lex specialist, that should not give rise to social problems, discrimination and legal uncertainty. Therefore, in the future it is necessary to formulate an ideal pattern that can achieve the achievement of employment goals while providing proper protection to employees who are citizens. For this reason, this paper will compare the existing legal arrangements for the transition of status that have existed to draw a line of problems that will be followed by a solution. This writing is normative legal research. There are at least four legal provisions for the transition of employment status that will be compared, namely the Village Secretary, staff of Corruption Eradication Commission as anti-corruption agency in Indonesia, and workers who switch to employees of the National Research and Innovation Agency.